2017
DOI: 10.1161/hypertensionaha.117.09016
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid Modulates Clinical Responses to Oral Nitrite and Nitrate

Abstract: Dietary nitrate (NO3−) and nitrite (NO2−) support nitric oxide (·NO) generation and downstream vascular signaling responses. These nitrogen oxides also generate secondary nitrosating and nitrating species that react with low molecular weight thiols, heme centers, proteins and unsaturated fatty acids. To explore the kinetics of NO3− and NO2− metabolism and the impact of dietary lipid on nitrogen oxide metabolism and cardiovascular responses, the stable isotopes Na15NO3 and Na15NO2 were orally administered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…More recently, the clinical administration of 15 N-labeled nitrite and nitrate has convincingly shown that fatty acid nitration occurs in humans during digestion (Fig. 1) (80,81). This observation in turn motivated the proposal that the cardiovascular benefits of a Mediterranean-like diet, rich in both vegetable-derived NO 2 − and NO 3 − and marine or olive oil-derived unsaturated fatty acids, could be (in part) ascribed to increased NO 2 -FA generation and the downstream elevation of vasoactive and anti-inflammatory lipid mediators (82).…”
Section: Critical Issues and Novel Insights Regarding The Unique Nmentioning
confidence: 95%
“…More recently, the clinical administration of 15 N-labeled nitrite and nitrate has convincingly shown that fatty acid nitration occurs in humans during digestion (Fig. 1) (80,81). This observation in turn motivated the proposal that the cardiovascular benefits of a Mediterranean-like diet, rich in both vegetable-derived NO 2 − and NO 3 − and marine or olive oil-derived unsaturated fatty acids, could be (in part) ascribed to increased NO 2 -FA generation and the downstream elevation of vasoactive and anti-inflammatory lipid mediators (82).…”
Section: Critical Issues and Novel Insights Regarding The Unique Nmentioning
confidence: 95%
“…The endogenous formation of NO 2 -FA [ [3] , [4] , [5] ] will be strongly influenced by diet, which may contain pre-formed NO 2 -FA or a combination of precursor fatty acids and sources of the organic nitrates required for fatty acid nitration (i.e., NO 2 − coming from animal and plant-derived products or NO 2 − -based preservatives) [ 22 ]. Clinical studies have revealed that dietary supplementation of organic nitrates, with and without co-administration of conjugated linoleic acid (cLA), resulted in a sustained level of NO 2 -cLA only when cLA was co-administered [ 23 ]. This indicates that cLA is rate limiting and its simultaneous presence in the gastric compartment together with NO 2 − and its precursor nitrate (NO 3 − ) is needed for the formation of the NO 2 -cLA.…”
Section: Introductionmentioning
confidence: 99%
“…Thus endogenous nitrated fatty acids may have a role in modulating the activity of nociceptive afferents and, in turn, influence the development and/or resolution of inflammatory responses and pain. The demonstration that oral administration of nitrated fatty acids or their precursors can produce significant blood, tissue and urine levels of these substances [3,4345] raises the possibility that nitro-lipid therapies may be developed to target pathophysiological mechanisms and disorders which involve TRP channels [46] and that passage of these substances from the urine into the bladder wall might be effective in treating certain types lower urinary tract dysfunctions.…”
Section: Resultsmentioning
confidence: 99%